2000
DOI: 10.1046/j.1365-2133.2000.03895.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of real‐time and store‐and‐forward teledermatology: a cost–benefit study

Abstract: The store-and-forward consultation was cheaper, but less clinically efficient, compared with the real-time consultation. The absence of interaction in a store-and-forward consultation limits the dermatologist's ability to obtain clinically useful information in order to diagnose and manage a patient satisfactorily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 17 publications
2
84
0
3
Order By: Relevance
“…4 Three studies compared the two modes. 14,23,24 In one study, 23 patients were not seen in-person, while another found identical diagnoses with in-person for 64% of patients with greater agreement for live interactive than store-and-forward that was not statistically significant. 24 A third study showed combining methods significantly increases concordance with in-person exams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Three studies compared the two modes. 14,23,24 In one study, 23 patients were not seen in-person, while another found identical diagnoses with in-person for 64% of patients with greater agreement for live interactive than store-and-forward that was not statistically significant. 24 A third study showed combining methods significantly increases concordance with in-person exams.…”
Section: Introductionmentioning
confidence: 99%
“…14 Although live interactive and store-and-forward methods have been compared before 14,23,24 the studies comparing remote methods to in-person 14,24 used diagnoses of single inperson dermatologists. This study extends teledermatology research by directly comparing concordance between inperson, live interactive, and store-and-forward methods with two in-person dermatologists establishing a diagnostic comparison baseline, while also addressing confidence and biopsy decisions and effects of video quality in live interactive consultations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is a viable option for almost all medical specialties, particularly those for which images comprise the main diagnostic tool (4)(5)(6)(7) . Thus, the fields of radiology, dermatology, pathology, ultrasound, and ophthalmology, among others (8)(9)(10)(11)(12) , are especially favorable for the establishment of data transmission protocols with diagnostic purposes (13,14) . Ophthalmology, for example, can greatly benefit from telemedicine (15,16) , as it is crucial to identify patients that present urgent cases in order to avoid morbidity and permanent disorders (17) .…”
Section: Introductionmentioning
confidence: 99%
“…There are two possibilities for teleconsultation: store-and-forward and videoconferencing. Store-andforward teleconsultation is older and cheaper than videoconferencing -at least in dermatology [6,7], but the goal of both of them is to improve the health care delivery.…”
Section: Introductionmentioning
confidence: 99%